Australian Multiculturalism. Th e Roots of its Success .......... 109 - Ozdowski, Sev (Promoting Changes in Times of Transition and Crisis: Reflections on Human Rights Education, 2013)
Despite its racist past, high and diverse immigration and enormous cultural and reli-gious diversity, contemporary Australia is a highly successful and well functioning multi-cultural society. The paper will analyse the reasons behind this success.The paper starts with an examination of Australia’s history from early settlement, with special focus on Australia’s social justice ethos and egalitarianism, its initial reliance on mother England for migrants, economy, governance, culture, its self-imposed regional iso-lation and tight immigration controls. The focus will then shift to the unique Australian culture that has emerged today, com-bining the elements of past and present. The paper will explore policies, institutions and laws that facilitated the development of modern Australia and its national character. Spe-cific features of Australian multiculturalism are listed and discussed, including the open nature of Australian society, the significance of immigration controls and the evolution of the “fair go” concept.Finally, the paper will examine the key and sometimes unique factors that have made the success of Australian multiculturalism possible. Some of these factors may not be pre-sent in other societies, thus making advancement of social harmony difficult. Particular attention will be paid to Australian policy and legislative settings, as well as to the Austral-ian education system, all of which focus on inclusion and equity, celebrating the values that bring all Australians together.